Assessment of Body Condition Score of Ganjam Doe and its Relationship with Physical Attributes - Sahoo, S. R.; Ghosh, C. P.; Datta, S. (International Journal of Bio-resource and Stress Management, 2023)
The present work was designed during March to June, 2021 to study the Body Condition Score (BCS) of Ganjam doe in its native tract and to find out its relationship with various physical attributes such as body weight (BWT), pin shoulder length (PS), height at withers (HW), heart girth (HG), abdominal girth (AG) and thigh circumferences (TC) in the villages of Nayagarh district, Odisha, India. The study was conducted on 102 Ganjam does maintained in the farmers’herd. BCS scale of 1 to 5 with 0.5 increments was used to score the does. The does were divided into groups according to their age (up to 3 yrs and above 3 yrs). The number of does with BCS of 2.00, 2.50, 3.00, 3.50, 4.00 and 4.50 were 25, 10, 21, 4, 22 and 20, respectively. The mean BCS, BWT, PL, HW, HG, AG and TC of Ganjam goats were 3.24, 27.80 kg, 59.73 cm, 64.40 cm, 70.62 cm, 88.28 cm and 28.24cm, respectively. All the physical parameters showed an increased trend from BCS range of 2.00 to 4.50. However,does having BCS ranges within 3 to 4.5 were maximum in the population. The BCS, BWT and all physical parameters were significantly (p<0.05) higher in the flock above 3 yrs. The BCS was positive and significantly (p<0.01) correlated with BWT (0.974), PS (0.889), HW (0.919), HG (0.955), AG (0.833) and TC (0.509). BCS was used to evaluate feeding programs, judge health status, and make management decisions to maximize reproduction and output.